The Diagrammatic Soergel Category and sl(2) and sl(3) Foams - Pedro Vaz (International Journal of Mathematics and Mathematical Sciences, 2010)
We define two functors from Elias and Khovanov's diagrammatic Soergel category, one targeting Clark-Morrison-Walker's category of disoriented sl(2) cobordisms and the other targeting the category of (universal) sl(3) foams.